Composition-dependent transition from spin glass to ferrimagnet in CaLa2Ni2-xCuxWO9 (0 ≤ x ≤ 0.5) - Chin, C-M; Cassidy, SJ; Hunter, EC; Battle, P (Elsevier, 2020)
Polycrystalline samples of the monoclinic perovskites CaLa2Ni2-xCuxWO9 (x = 0.25 and 0.5) have been prepared and characterised by neutron diffraction and magnetometry. The Ni2+, Cu2+ and W6+ cations are partially ordered over two crystallographically-distinct six-coordinate sites such that one is ∼63% occupied by W6+ and both are occupied by Ni2+ and Cu2+ in a ratio of (2-x):x. The composition x = 0.25 behaves as a spin glass below 35 K whereas x = 0.5 is ferrimagnetic below 120 K with an ordered moment of 0.774(5) μB per magnetic cation. The atomic moments order in a G-type pattern and the imbalance in the number of magnetic cations on the two sites results in a net magnetisation.